Plan de mercadeo del producto compostpalm de la extractora agrícola rio manso s.a. de la provincia de Santo Domingo de los Tsáchilas, año 2015 - Gómez Pionce, Freddy Olmedo (2015)
Every company should have adequate Marketing Plans that allow through the design and implementation of strategies embodied in action programs achieve their objectives, which are routed towards improving the positioning of goods and / or services offered by the company.For this reason the company Extractora Agricola Río Manso S.A., requires that a Marketing Plan for your product Compostpalmis designed, in order to contribute to significantly improve its market' positioning organic fertilizers in the province of Santo Domingo Tsáchilas and surrounding areas, establishing different strategies; among which the promotion and advertising play an important role in the success of this plan, this will facilitate the activities of sales department, because customers today are unaware of the benefits, features and ways of using compost Compostpalm. This work is bibliographically titration substantiated through the use of books by renowned authors related to the research study the same as scientifically based the proposal put forward; texts being useful, because your important content guided the design and development of marketing plan for the product Compostpalmpertaining to Extractora Agricola Río Manso S.A.Through the implementation of customer surveys and interviews developed the General Manager of the company, it was determined that the company does not have a marketing plan where the objectives, strategies, action programs, detailing control mechanisms, inter alia potentializing product positioning Compostpalmin your target market.It is essential to note that the company currently there is no written or digital document to which resort to guide the various activities to be developed to position the product Compostpalm; therefore were designed and set each and every one of the activities to be performed for this purpose; plus the respective budget was prepared, and a series of performance indicators especially the sales area, to assess the achievements after it implemented the proposed marketing plan designed.Evaluating the results, we proceeded to the development of the marketing plan for the product Compostpalmbelonging to the company Extractora Agricola Río Manso S.A., the same being applied improve the positioning of the respective product on the market for organic fertilizers in the province of Santo Domingo de los Tsáchilas and its area of influence.This implementation shall have the respective follow in order to improve and update it periodically.